Commodification of Mobile Banking Interface Design for Elderly Users - Ginanjar Hamid Wiryawan; Achmad Syarief; Wegig Murwonugroho (Mudra Jurnal Seni Budaya, 2022)
The design planning of the Mobile Banking Interface Design for Elderly Users aims to redesign the mobile banking application interface to be more effective and easier for elderly users. This research uses a mixed-method of explanatory sequential, which sequentially uses quantitative and qualitative modes. The quantitative model uses questionnaires and bodystorming simulations to obtain data on the needs and behavior of the elderly. The qualitative model is based on the User-Centered Design (UCD) design process. The research resulted in the following: (1) data on the needs of elderly users when using mobile banking applications (2) data on the behavior of elderly users to better understand the interface of the mobile banking application. Based on these data, a mobile banking interface was developed to suit the needs of elderly users, which includes a more simplified display, enlarged text size, enlarged button size and additional spacing, adjusted icon shape to the understanding of elderly users, and display layout arrangements that are very concerned for making the interaction process more comfortable. Evaluation of the interface design results on mobile banking applications for elderly users shows that the application is more acceptable, more understandable, and easier for elderly use.